Salivary immunoglobulin A antibodies reacting with antigens from oral streptococci: longitudinal study in humans. - Gahnberg, L (1981)
The salivary immunoglobulin A (IgA) activity to antigens from four common oral streptococci was analyzed in samples from five humans. From each individual, parotid and whole saliva were collected 12 times over a period of 4 months. In samples collected at different occasions, the salivary IgA activity varied considerably. The variations showed a covariation with the concentration of total IgA in the saliva samples. A covariation was also found between salivary IgA antibodies of different specificity. It is concluded that reference antigens, in combination with measurement of total IgA concentration, ought to be used when evaluating the salivary IgA response in humans.